Research as/for Reconceptualizing Learning in Nepal: A Praxis of a Teacher-Researcher - Shrestha, Raju (Journal of Transformative Praxis, 2022)
This paper is an outcome of my MPhil dissertation, in which I was engaged in transformative research practice to critically look into the learning practices that I followed in my non/academic journey from my childhood education to my MPhil research period. The learning practices can be inevitable approaches to transformative learning but might not have been given a space in the educational context of Nepal. Keeping this in consideration, I, as a transformative teacher-researcher, attempt to re-conceptualize learning practices in Nepal by breaking the beliefs taken for granted that learning takes place only within the classroom guided by teachers’ pedagogical practices. In other words, I make an argument for the approaches to transformative learning apart from classroom pedagogy. In doing so, I reflect on my learning journey by responding to the guiding research question, ‘How did I adopt transformative learning practices apart from classroom pedagogy from my childhood education to MPhil research?’ For this, I engage in critical self-reflection on my learning practices using a multi-paradigmatic (interpretivism, criticalism, postmodernism) research approach and autoethnography as a research method to capture my autobiographical learning journey from childhood education to my MPhil degree. I conclude the paper by providing my transformative learning practices: learning beyond the classroom context, learning through critical reflection, learning through a disorienting dilemma, learning through writing about self and others, learning through perspectival meaning-making and learning through envisioning by critically looking through the lens of knowledge constitutive interests and transformative theories. The theories help me in the process of analyzing, interpreting and making meaning of my experience.Further, the theories support me to orient my arguments toward transformative education by deconstructing the taken-for-granted teaching and learning practices of teachers, practitioner-researchers and educators in the context of Nepal.